Fermentasi Bagase Tebu Dengan Neurospora sitophila dan Pengaruhnya Terhadap Nilai Gizi dan Kecernaan Secara in Vitro - Nurhaita Nurhaita; N Definianti; R Zurina (Jurnal Embrio, 2012)
This study aimed to evaluate the effect of fermentation on the nutritional value and digestibility of sugarcane bagase. Research is using completely randomized design with 4 treatments and 4 replications. The treatments tested were several levels of inoculum Neurospora sitophila ie A = 0%; Neurospora sitophila; B = 2% Neurospora sitophila; C = 4% Neurospora sitophila and D = 6% Neurospora sitophila. Parameters measured were 1. Nutritional value of sugarcane bagase fermentation (dry matter, crude protein, crude fiber and crude fat) and 2. The content of the fiber fraction (NDF, ADF, cellulose, hemicellulose and lignin) 3. In-vitro digestibility of dry matter and organic matter. The results showed that the inoculum level of Neurospora sitophilla on the fermentation significantly improve the quality of sugarcane bagase, this is reflected in the increase in crude protein content of 2.34% to 3.52%, a decrease in crude fiber content of 39.92% to 31, 25%. Lignin content of fermented sugar cane decrease from 8.74% to 7.20%. This matter caused increased on in-vitro digestibility of dry matter from 46.48% to 56.46% and the digestibility of organic matter increased from 48.19% to 56.32%. From this study it can be concluded that fermentation with Neurospora sitophilla can enhance the nutritional value and digestibility of sugarcane bagase. The best inoculum level of Neurospora sitophilla is 6%.